The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4070/kcj.2013.43.10.664
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ischemic Time on the Predictive Value of High-Sensitivity C-Reactive Protein in ST-Segment Elevation Myocardial Infarction Patients Treated by Primary Percutaneous Coronary Intervention

Abstract: Background and ObjectivesThe high-sensitivity C-reactive protein (hs-CRP), a marker of inflammation, has been known to be elevated in patients with coronary artery disease. However, there is controversy about the predictive value of hs-CRP after acute myocardial infarction (MI). Therefore, we evaluated the impact of ischemic time on the predictive value of hs-CRP in ST-segment elevation myocardial infarction (STEMI) patients who were treated by primary percutaneous coronary intervention (PCI).Subjects and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…However, there were no significant correlations between MACEs and elevated CRP after PCI in our study. Other studies [32][33][34] also reported that elevated CRP levels reflect MACE in patients with ACS. Some reports [35,36] defined MACEs as pure coronary events such as target vessel revascularization, MI, and in-stent restenosis.…”
Section: Discussionmentioning
confidence: 89%
“…However, there were no significant correlations between MACEs and elevated CRP after PCI in our study. Other studies [32][33][34] also reported that elevated CRP levels reflect MACE in patients with ACS. Some reports [35,36] defined MACEs as pure coronary events such as target vessel revascularization, MI, and in-stent restenosis.…”
Section: Discussionmentioning
confidence: 89%
“…The influence of other risk factors on CRP values such as smoking cigarettes, presence of arterial hypertension, or even female gender are reported in some papers [18][19][20] . Prolonged ischemic time has also influence on the increased CRP levels 21 . However, in the multivariate survival analyses, when putting all these risk factors into one model using the Cox regression, CRP still emerges as the best independent predictor of early mortality in the patients without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible answers might be that the acute glucose fluctuation in the nondiabetic STEMI patients triggers more oxidative stress compared with sustained chronic hyperglycemia in the patients with diabetes type 2 22 . It is also known that acute hyperglycemia in STEMI is an independent risk factor for adverse events and that can even potentiate stress-induced apoptosis [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…The ischemic time might, in part, also explain the higher hs-CRP levels in these patients at baseline. We also measured hs-CRP at 2 weeks, 7 weeks and 4 months after admission, and in addition to Patti et al we report on the temporal course of hs-CRP in STEMI patients [8,9,18,19]. In addition, we used more sensitive assay to determine the hs-CRP levels, allowing detection of CRP below 5 mg/l and facilitating the detection of subtle differences between patients with normal and impaired reperfusion.…”
Section: Temporal Course Of Hs-crpmentioning
confidence: 92%
“…Previous data suggested that a higher level of hs-CRP (≥3 mg/l) is an independent predictor of long-term clinical outcomes in late-presenting STEMI patients (i.e. ischemia time ≥ 6 h) [18]. We investigated whether ischemia time, hsCRP and reperfusion were associated.…”
Section: Hs-crp and Ischemia Time As Predictors For Reperfusionmentioning
confidence: 97%